2016
DOI: 10.1074/jbc.m116.723239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PIWIL4, an Argonaute Family Protein, in Breast Cancer

Abstract: P-element-induced wimpy testis (PIWI) proteins bind to PIWI-interacting RNAs and play key roles in the biogenesis and functions of PIWI-interacting RNAs. It has been reported that PIWI proteins are essential for stem cell self-renewal and germline development in diverse organisms and that they are ectopically expressed in multiple forms of cancer. However, the role of PIWI in cancer remains elusive. Here we report that one of the four PIWI proteins in humans, PIWIL4, is highly expressed in both breast cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…To test for DDX4 expression, we first screened for transcripts using RT‐PCR for each cell line. Expression of another germline factor PIWI‐like2 (PIWIL2) that is known to function with DDX4/Vasa in the germline as well as in some cancer cells was analyzed in parallel. We learned that both ddx4 and piwil2 mRNA were expressed in IM‐9 and THP‐1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test for DDX4 expression, we first screened for transcripts using RT‐PCR for each cell line. Expression of another germline factor PIWI‐like2 (PIWIL2) that is known to function with DDX4/Vasa in the germline as well as in some cancer cells was analyzed in parallel. We learned that both ddx4 and piwil2 mRNA were expressed in IM‐9 and THP‐1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Nanos (RNA‐binding protein) upregulation as a consequence of Rb (Retinoblastoma) inactivation causes inhibition of apoptotic genes and promotes cell proliferation . PIWI (a small RNA regulator) has been reported to be linked to many hallmarks of cancer, including cell proliferation, anti‐apoptosis, genomic instability, and metastasis . These emerging functions of germline factors led us to suggest that germline factors may contribute broadly to cancer cell regulation.…”
mentioning
confidence: 99%
“…Apart from modulation of Akt pathway, we observed significant variation in the phosphorylation levels of STAT3, p53, AMPKα and HSP90 21 . In the similar line, Wang et al have also shown the influence of HIWI2 in the activation of MAPK/ERK, TGFβ and FGF signalling pathways 50 . It is plausible that these changes could be mediated through piRNAs, suggesting its involvement in cell signalling and cell-cell contact.…”
Section: Andmentioning
confidence: 74%
“…Similarly, PIWI proteins also have significant roles in different cancers such as breast cancer. In spite of extensive research about cancer, only recent articles have discussed PIWI proteins roles in this area [86]. PIWIL4 Gene is one of the upregulated genes in breast cancer which is highly expressed not only in breast cell lines but also in breast cancer samples.…”
Section: Piwi Proteins and Breast Cancermentioning
confidence: 99%